Effect of Supervision on Teacher Performance in PAUD Groups Playing Kasih Bunda, East Lampung - Maharani, Rahi Tyas; Yahya , Yahya; Putra, Nanda Pramana; Pramono, Arief (Penerbit Goodwood, 2025)
Purpose: This study aimed to examine the effect of supervision on teacher performance in the PAUD Kasih Bunda Playgroup in East Lampung. This study seeks to identify the extent to which supervision enhances teacher productivity and learning quality. Research methodology: A quantitative descriptive approach was applied with a total population sample of 21 teachers. Data were collected through questionnaires, interviews, observations, and document analysis. The validity and reliability of the instruments were tested using SPSS 21, and regression analysis was employed to measure the effect of supervision on teacher performance. Results: The findings revealed a strong correlation (r = 0.732) between supervision and teacher performance, with a determination coefficient (R²) of 53.6%. Regression analysis indicated that supervision significantly affected teacher performance, with every one-point increase in supervision associated with a 0.505-point improvement in teacher performance. Conclusions: Effective supervision positively influences teacher performance, highlighting its importance in improving the planning, implementation, and evaluation of learning. Regular supervisory visits, constructive feedback, and collaborative guidance can enhance the quality of teaching and foster better student outcomes. Limitations: This study focused on only one institution with a relatively small sample size, limiting the generalizability of the findings. It also does not account for other influencing factors, such as work motivation, leadership, or organizational culture. Contribution: This study provides empirical evidence of the critical role of supervision in strengthening teacher performance in early childhood education. This study contributes to the literature on educational management and offers practical insights for school leaders, supervisors, and policymakers to enhance teacher quality through structured supervision.